Urbanization and Agglomeration Benefits : Gender Differentiated Impacts on Enterprise Creation in India's Informal Sector - Ghani, Ejaz; Kanbur, Ravi; O'Connell, Stephen D. (World Bank, Washington, D.C., 2013)
This paper presents an exploration at the intersection of four important themes in the current development discourse: urbanization, agglomeration benefits, gender and informality. Focusing on the important policy objective of new enterprise creation in the informal sector, it asks and answers four specific questions on the impact of urbanization and gender. It finds that (i) the effect of market access to inputs, on creation of new enterprises in the informal sector, is greater in more urbanized areas; (ii) This "urbanization gradient" also exists separately for the creation of female owned enterprises and male owned enterprises; (iii) there is a differential impact of female specific market access compared to male specific market access, on female owned enterprise creation in the informal sector ; and (iv) gender specific market access to inputs matters equally in more or less urbanized areas. Among the policy implications of these findings are that (i) new enterprise creation by females can be encouraged by urbanization, but (ii) the effect can be stronger by improving female specific market access, especially to inputs. The analysis in this paper opens up a rich research agenda, including further investigation of the nature of input based versus output based perspectives on agglomeration benefits, and exploration of policy instruments that can improve female specific market access, which is shown to increase female owned enterprise creation.